A new organic solvent tolerant protease from Bacillus pumilus 115b - Raja Abdul Rahman, Raja Noor Zaliha; Mahamad, Shalihah; Salleh, Abu Bakar; Basri, Mahiran (Springer, 2007)
Five out of the nine benzene–toulene–ethylbenzene-xylene (BTEX) tolerant bacteria that demonstrated high protease activity on skim milk agar were isolated. Among them, isolate 115b identified as Bacillus pumilus exhibited the highest protease production. The protease produced was stable in 25% (v/v) benzene and toluene and it was activated 1.7 and 2.5- fold by n-dodecane and n-tetradecane, respectively. The gene encoding the organic solvent tolerant protease was cloned and its nucleotide sequence determined. Sequence analysis revealed an open reading frame (ORF) of 1,149 bp that encoded a polypeptide of 383 amino acid residues. The polypeptide composed of 29 residues of signal peptide, a propeptide of 79 residues and a mature protein of 275 amino acids with a calculated molecular mass of 27,846 Da. This is the only report available to date on organic solvent tolerant protease from B. pumilus.